Determinación de Zonas Aptitudinales para los Cultivos de Maíz (zea mays), papa (solanum tuberosum) y Chocho (lupinus mutabilis), Mediante un Modelo Geográfico en la Parroquia de Alaquez, Cantón Latacunga, Provincia de Cotopaxi, en el periodo 2018-2019. - Guaña Flores Manolo Sebastián (2019)
The objective of the research project was to establish sectors with the best edaphoclimatic conditions in the area under study which can help to the establishment and corn production (Zea mays), potato (Solanum tuberosum) and chocho (Lupinus mutabilis) crops, considering different variables such as temperature, precipitation, soil texture, cationic exchange, pH, MO and N. P, K, necessary for the production of these crops. Subsequently, a geographic model will be developed according to the needs of these crops, for the analysis of variables and results, the ARC GIS version 10.3 program will be used. It was based on the collection of 60 random soil samples in Alaquez Parish, which were interpolated with precipitation and temperature data provided by INAMHI, with the purpose of determining the best areas with edaphoclimatic conditions, supported in the documentation and bibliographic source. The method is based on remote sensing with the application of the structured query language (SQL) technique. This work will serve as an informative tool for the farmers of San Antonio de Alaquez parish, focusing especially on medium and small producers which are dedicated to the corn production (Zea mays), potato (Solanum tuberosum) and chocho ( Lupinus mutabilis), to obtain better crop yields, in addition to providing information on the edaphological and climatological requirements necessary for the correct zoning of the different species and thus helping the correct performance of agricultural production based on the soil-water relationship- plant.